Yield and nutrient uptake of rice (Oryza sativa) as influenced by sources and levels of phosphorus and zinc under trans- planted conditions - C.P. RAO; D.N. SHUKLA (Indian Journal of Agronomy, 2001)
A field experiment conducted during rainy season of 1993 and 1994 at Varanasi indicated that highest grain yield of rice (Oryza sativa L.) was recorded with ammo- nium polyphosphate (APP) at 90 kg P,OJha in combination with 30 kg ZnS0,lha. Total nutrient uptake of N, P, K and Zn was positively influenced by sources and levels of phosphorus and zinc rates. Among the sources of phosphorus tested, am- monium polyphosphate (APP) followed by Urea nitric phosphate (UNP) recorded the highest grain yield and nutrient uptake than diammonium phosphate (DAP). Increas- ing the doses of phosphorus from 30 to 90 kg P,O,lha, application of 60 kg P,O,lha through APP in combination with 30 kg ZnS0,lha was found to be the best for obtain- ing economical yield and higher nutrient uptake values of transplanted rice crop.
Keywords: Nutrient uptake; Sources; Phosphorus; Zinc